Endogenous H(2)S in hemorrhagic shock: innocent bystander or central player? - Calzia, Enrico (BioMed Central, 2012)
The role of the gaseous mediator hydrogen sulfide (H(2)S) in hemorrhagic shock is still a matter of debate. This debate is emphasized by the fact that available literature data on blood and tissue H(2)S concentrations vary by three orders of magnitude, both under physiological conditions as well as during stress states. Therefore, in a rat model of unresuscitated, lethal hemorrhagic shock, Van de Louw and Haouzi tested the two hypotheses of whether blood and tissue H(2)S levels would increase due to the shock-related tissue hypoxia, and whether vitamin B12 would attenuate organ injury and improve survival as a result of enhanced H(2)S oxidation. Hemorrhage did not affect the blood and tissue H(2)S content, and, despite the increased capacity to oxidize H(2)S, vitamin B12 did not affect any parameter of shock severity. The authors concluded that H(2)S concentrations cannot be used as a marker of shock, most probably as a result of tissue's capacity to oxidize H(2)S even under conditions of severe oxygen debt. This research paper elegantly re-adjusts the currently available data on blood and tissue H(2)S levels, and thereby adds an important piece to the puzzle of whether H(2)S release should be enhanced or lowered during stress conditions associated with tissue hypoxia.